Imine resveratrol analogs (IRAs): The strong antioxidant that can protect lymphocytes from oxidative damage. Issue 3 (28th December 2021) - Kubalová, Ivona; Šeršeň, František; Gálová, Eliška; Filo, Juraj
Abstract: Imine resveratrol analogs (IRAs) are promising new agents that can have higher positive effects and, simultaneously, lower negative properties than resveratrol. In this study, three imine hydroxy derivatives (2‐((4‐hydroxyphenylimino) methyl) phenol [IRA1], 3‐((4‐hydroxyphenylimino) methyl) phenol [IRA2], and 4‐((4‐hydroxyphenylimino) methyl) phenol [IRA3]) were prepared and tested in several biological assays. They performed superior to resveratrol in several antioxidant and biological assays, showing high antioxidant capacity and low genotoxicity. Ferric reducing antioxidant power assay (FRAP) and hydroxyl radicals scavenging assay revealed good Fe 3+ to Fe 2+ reduction and strong inhibition of hydroxyl radical formation, respectively. High dosage (1 mmol/dm 3 ) of IRA2 and IRA3 did not cause genotoxicity in human lymphocytes. Moreover, lymphocytes pretreated with all three IRAs accumulated only very few DNA breaks induced by H2 O2 than lymphocytes pretreated with resveratrol. Additionally, the number of detected DNA breaks appearing after removal of damaged DNA bases, 8‐oxo‐7, 8‐dihydroguanine (8‐oxoG), did not dramatically increase in lymphocytes treated with IRA2. Thus, we concluded that IRAs, especially IRA2, are strong antioxidants with the ability to protect lymphocytes from oxidative damage.